Sosialisasi dan Pendampingan Penggunaan Online Single Submission pada Pelaku Usaha Kecil dan Menengah di Kota Depok - Maya Puspita Dewi; Tuswoyo Tuswoyo; Abdul Gofur; Dony Hendarto (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
As an innovation, Online Single Submission is expected to guarantee the certainty of licensing which has been considered complicated and inefficient. In its development, electronic-based licensing did not work as expected. Lack of socialization and assistance for the Small and Medium Enterprises, has an impact on the low level of their understanding. The target activity is the Small and Medium Enterprises in Depok City. The activities went very well. The obstacle to this activity is the lack of supporting tools.